Modification of the Homotopy Perturbation Method and It’s Convergence - AYATI, Zainab; BIAZAR, Jafar (Walailak Journal of Science and Technology (WJST), 2014)
There are some methods to obtain approximate solutions of functional equations. One of them is the homotopy perturbation method. However, computing coefficients of pj, is time-consuming and challenging. In order to deal with this problem, a new modified homotopy perturbation method is introduced, which doesn’t need computations of the coefficients of pj. Here, the method has been applied to solve some examples and the results have been compared with those obtained from the homotopy perturbation method. Moreover, convergence of the method has been discussed. doi:10.14456/WJST.2014.15